Glioblastoma stem cell-derived exosomes induce M2 macrophages and PD-L1 expression on human monocytes. (3rd April 2018) - Gabrusiewicz, Konrad; Li, Xu; Wei, Jun; Hashimoto, Yuuri; Marisetty, Anantha L.; Ott, Martina; Wang, Fei; Hawke, David; Yu, John; Healy, Luke M.; Hossain, Anwar; Akers, Johnny C.; et al.
ABSTRACT: Exosomes can mediate a dynamic method of communication between malignancies, including those sequestered in the central nervous system and the immune system. We sought to determine whether exosomes from glioblastoma (GBM)-derived stem cells (GSCs) can induce immunosuppression. We report that GSC-derived exosomes (GDEs) have a predilection for monocytes, the precursor to macrophages. The GDEs traverse the monocyte cytoplasm, cause a reorganization of the actin cytoskeleton, and skew monocytes toward the immune suppresive M2 phenotype, including programmed death-ligand 1 (PD-L1) expression. Mass spectrometry analysis demonstrated that the GDEs contain a variety of components, including members of the signal transducer and activator of transcription 3 (STAT3) pathway that functionally mediate this immune suppressive switch. Western blot analysis revealed that upregulation of PD-L1 in GSC exosome-treated monocytes and GBM-patient-infiltrating CD14 + cells predominantly correlates with increased phosphorylation of STAT3, and in some cases, with phosphorylated p70S6 kinase and Erk1/2. Cumulatively, these data indicate that GDEs are secreted GBM-released factors that are potent modulators of the GBM-associated immunosuppressive microenvironment.